2022
DOI: 10.1177/01945998221089826
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Facility Volume on Patient Safety Indicator Events After Transsphenoidal Pituitary Surgery

Abstract: Objectives To investigate the impact of facility volume on Patient Safety Indicator (PSI) events following transsphenoidal pituitary surgery (TSPS). Study Design Retrospective database review. Setting National Inpatient Sample database (2003-2011). Methods The National Inpatient Sample was queried for TSPS cases from 2003 to 2011. Facility volume was defined by tertile of average annual number of TSPS procedures performed. PSIs, based on in-hospital complications identified by the Agency of Healthcare Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
3
3
0
Order By: Relevance
“…1 Consistent with our results, we agree with their findings further supporting our conclusion that patients treated at HVFs experienced superior outcomes following endoscopic TSPS. 1 As noted in Chalif's and Aghi's letter, better operative skills and perioperative care developed at HVFs are particularly significant in affecting outcomes for certain patient subgroups such as the elderly. 2 The use of patient safety indicator events (PSIs) draws attention to complications related to operative and perioperative care and our results indicated that PSIs were significantly lower in HVFs compared to non-HVFs.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…1 Consistent with our results, we agree with their findings further supporting our conclusion that patients treated at HVFs experienced superior outcomes following endoscopic TSPS. 1 As noted in Chalif's and Aghi's letter, better operative skills and perioperative care developed at HVFs are particularly significant in affecting outcomes for certain patient subgroups such as the elderly. 2 The use of patient safety indicator events (PSIs) draws attention to complications related to operative and perioperative care and our results indicated that PSIs were significantly lower in HVFs compared to non-HVFs.…”
supporting
confidence: 93%
“…According to their letter, results from the National Cancer Database (NCDB) showed that adults undergoing endoscopic TSPS experienced decreased mortality and length of stay at high-volume facilities (HVFs) compared to non-HVFs. 1 Consistent with our results, we agree with their findings further supporting our conclusion that patients treated at HVFs experienced superior outcomes following endoscopic TSPS. 1 As noted in Chalif's and Aghi's letter, better operative skills and perioperative care developed at HVFs are particularly significant in affecting outcomes for certain patient subgroups such as the elderly.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…1 As noted in Chalif's and Aghi's letter, better operative skills and perioperative care developed at HVFs are particularly significant in affecting outcomes for certain patient subgroups such as the elderly. 2 The use of patient safety indicator events (PSIs) draws attention to complications related to operative and perioperative care and our results indicated that PSIs were significantly lower in HVFs compared to non-HVFs. HVFs, as demonstrated in the NCDB and National Inpatient Sample, provide superior care for endoscopic TSPS patients.…”
mentioning
confidence: 80%